Pre-aging combined with multi-stage rolling processing: Enhancing precipitate-dislocation interaction for strengthening of Cu-Cr-Zr-Ni-Si alloy - Xiangyi Jiao; Zihao Zhang; Hua Ding (Materials & Design)
The low strength of high-conductivity Cu-Cr-Zr alloys has restricted their application in micro-structural lead frames. This study introduces pre-aging multi-stage rolling processes to generate high-density dislocations via pre-precipitated Cr phases in a Cu-Cr-Zr-Ni-Si alloy, enhancing its hardening effect. The results show that the alloy processed by this thermomechanical treatment achieves an excellent combination of strength and conductivity: a tensile strength of ∼680 MPa and electrical conductivity near 70 % IACS. Pre-aging modifies the geometric features of Cr precipitates, promoting strong interactions with dislocations during subsequent cold rolling. Hardening model calculations indicate that the alloy’s reinforcement stems from the dislocation density strengthening and precipitation hardening. This work demonstrates that the pre-aging multi-stage rolling process can produce materials with superior comprehensive properties, holding promise for large-scale industrial applications of high-strength, high-conductivity copper alloys.